A European survey of older peoples' preferences, and perceived barriers and facilitators to inform development of a medication-related fall-prevention patient portal - Ploegmakers, Kim J; Linn, A J; Medlock, S; Seppälä, L J; Bahat, G; Caballero-Mora, M A; Ilhan, B; Landi, F; Masud, T; Morrissey, Y; Ryg, J; Topinkova, E; et al. (European geriatric medicine, 2024)
PURPOSE: Falls are a major and growing health care problem in older adults. A patient portal has the potential to provide older adults with fall-prevention advice to reduce fall-risk. However, to date, the needs and preferences regarding a patient portal in older people who have experienced falls have not been explored. This study assesses content preferences, potential barriers and facilitators with regard to using a patient portal, as perceived by older people who have experienced falls, and explores regional differences between European participants. METHODS: We conducted a survey of older adults attending an outpatient clinic due to a fall or fall-related injury, to explore their content preferences, perceived barriers, and facilitators with respect to a fall-prevention patient portal. Older adults (N = 121, 69.4% female, mean age: 77.9) were recruited from seven European countries. RESULTS: Almost two-thirds of respondents indicated they would use a fall-prevention patient portal. The portal would preferably include information on Fall-Risk-Increasing Drugs (FRIDs), and ways to manage other related/relevant medical conditions. Facilitators included a user-friendly portal, with easily accessible information and physician recommendations to use the portal. The most-commonly-selected barriers were privacy issues and usage fees. A family member's recommendation to use the portal was seemingly more important for Southern and Eastern European participants compared to the other regions. CONCLUSION: The majority of older people with lived falls experience expressed an interest in a fall-prevention patient portal providing personalized treatment advice to prevent further falls. The results will be used to inform the development of a fall-prevention patient portal. The fall-prevention patient portal is intended to be used in addition to a consultation with a physician. Future research is needed to explore how to prevent falls in older patients who are not interested in a fall-prevention patient portal.
Keywords: senioři; senioři nad 80 let; pacientova volba; Patient Preference; portál pacienta; Europe; Evropa; průzkumy a dotazníky; mužské pohlaví; Patient Portals; Aged, 80 and over; ženské pohlaví; Humans; Surveys and Questionnaires; Female; Aged; úrazy pádem; Accidental Falls; lidé; Male